2020
DOI: 10.14419/ijans.v9i1.30456
|View full text |Cite
|
Sign up to set email alerts
|

Dietary knowledge, attitude, and practice regarding prevention of iron deficiency anemia among pregnant women in Riyadh, Saudi Arabia

Abstract: Background: Iron deficiency anemia (IDA) is recognized as the world’s most widespread nutritional disorder, affecting 1.6 billion people that constitute about 25% of the global population, and it is one of the most common diseases complicating antenatal women worldwide, particularly in the developing countries. There have been few research studies on IDA in pregnancy in Arab countries including Saudi Arabia.Objectives: This study aimed to assess the knowledge, attitude, and practice (KAP) on IDA among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…This may account for the fair knowledge (91.3%) of anemia in pregnant women with high education. This finding is consistent with studies in different countries, where adherence to anemia prevention measures was more likely to be with women with higher education [15,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may account for the fair knowledge (91.3%) of anemia in pregnant women with high education. This finding is consistent with studies in different countries, where adherence to anemia prevention measures was more likely to be with women with higher education [15,24].…”
Section: Discussionsupporting
confidence: 92%
“…The possible reason for this difference in the knowledge of anemia among pregnant women might be the study context and the socio-economic characteristics of the study participants. Also, the result of this study is much lower than a study done in Saudi Arabia, which reported that 94% of pregnant women had good knowledge of anemia [24]. The possible reason for this difference in the knowledge of gestational anemia might be due to the difference in the socio-economic status of the women.…”
Section: Discussioncontrasting
confidence: 84%
“…Having a secondary, and diploma and above an educational level increases the knowledge of anemia. This is supported by studies done in southern Ethiopia, 33 West Shewa zone, Ethiopia, 30 Ghana, 23 India, 42 Kathmandu, Nepal, 34 Riyadh, Saudi Arabia, 41 and Baghdad. 39 Similarly, secondary and diploma, and above educational level also increase the adherence to anemia prevention strategies by 2.25 and 2.39 times respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, the result of our study is much lower than a study done in Riyadh, Saudi Arabia reported that 94% of the pregnant women had good knowledge of anemia. 41 This possible reason for this difference in the knowledge of anemia might be due to the difference in the socio-economic status and educational level of the study participants.…”
Section: Discussionmentioning
confidence: 97%